Penatalaksanaan Holistik Laki-laki Usia 22 Tahun Dengan Dermatitis Kontak Alergi Melalui Pendekatan Kedokteran Keluarga: Sebuah Laporan Kasus - Canthika Hairil, Nabilla Ayu; Pratiwi, Dian; Nasution, Syahrul Hamidi (CV. Jasa Sukses Abadi, 2024)
Allergic contact dermatitis (DKA) is caused by antigens (allergens) which give rise to type IV hypersensitivity reactions. In Indonesia, it was shown that 97% of 389 cases were contact dermatitis, 66.3% of them were irritant contact dermatitis and 33.7% were allergic contact dermatitis. Applying the principles of a holistic and comprehensive family doctor approach in detecting risk factors, clinical problems, and patient management based on evidence-based medicine and being family-approached and patient-centered. This study is a case report. Primary data was obtained through history taking and physical examination. Secondary data was obtained from patient medical records at the Community Health Center. Assessment is based on a holistic diagnosis of the beginning, process and end of the study quantitatively and qualitatively. Patient Mr. I, 22 years old, came to the Simpur Community Health Center clinic with complaints of red, scaly patches appearing, accompanied by itching on both legs and since 2 months ago until now. Initially, the patient was exposed to stagnant water at his workplace. Over time, the patient complained of reddish rashes accompanied by itching. The patient wore socks and shoes the next day, complaining that the reddish rashes were becoming more numerous and the itching on both feet was getting worse. The patient worked as a construction worker. The patient was diagnosed with allergic contact dermatitis. There are several factors that influence the patient's condition, namely internal and external risk factors. Holistic management with a family doctor approach is needed for patients with allergic contact dermatitis in identifying problems in various aspects to support the success of therapy.